1992
DOI: 10.1029/92wr01764
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterns of throughfall and soil water dynamics in a Douglas fir stand

Abstract: Measured spatial patterns of water uptake were found to be related to measured throughfall patterns around trees, especially in dry months. To simulate these lateral feedback mechanisms, the one-dimensional soil water model SWlF was modified to a quasi-three-dimensional model allowing preferential water uptake from wet sites. Input-output relations, linking soil physical input parameters to simulation results, showed that soil water contents at field capacity and those after a dry period in summer could be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
93
2
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 11 publications
4
93
2
1
Order By: Relevance
“…In the context of the relations between tree structure and tree function, direct throughfall and stemflow induce spatial variability of rainfall water at the ground surface (e.g. [3,49,83] figure 3b) which has been correlated to the distribution of superficial fine roots [49] and soil water uptake [10]. Rainfall interception may therefore be regarded as the first step of water resource partitioning between plants, i.e.…”
Section: Rainfall Interceptionmentioning
confidence: 99%
“…In the context of the relations between tree structure and tree function, direct throughfall and stemflow induce spatial variability of rainfall water at the ground surface (e.g. [3,49,83] figure 3b) which has been correlated to the distribution of superficial fine roots [49] and soil water uptake [10]. Rainfall interception may therefore be regarded as the first step of water resource partitioning between plants, i.e.…”
Section: Rainfall Interceptionmentioning
confidence: 99%
“…Nevertheless, Kern (1966), Bouten et al (1992) and Keim et al (2005) have documented a significant relation between a vertically downward projected canopy structure and rain through fall distribution. Moreover, at the withinstand level, differences between the chemical properties of through fall have been found and spatially linked to the crown positions (Beier et al 1993;Whelan et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Distribution of precipitation depends on the tree species and the age of the trees (Ford and Deans, 1978;Kantor, 1985;Johnson, 1990;Loustau et al, 1992;Levia and Frost, 2003;Van Stan et al, 2011). Stemflow generated between condominant tree species may be highly affected by wind and the spatial variability of throughfall was also documented (Bouten et al, 1992;Keim et al, 2005;Holko, 2010Holko, , 2011. Concentrations of dissolved substances in throughfall and stemflow may be considerably different (Kantor, 1985;Raubuch et al, 1998;Oulehle and HruĆĄka, 2005;Devlaeminck et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of dissolved substances in throughfall and stemflow may be considerably different (Kantor, 1985;Raubuch et al, 1998;Oulehle and HruĆĄka, 2005;Devlaeminck et al, 2005;. It was shown that the spatially distributed infiltration under the forest canopy caused a significantly variable water regime (Bouten et al, 1992;Raat et al, 2002;Liang et al, 2007Liang et al, , 2009Guswa and Spence, 2012;Guswa et al, 2012) and soil solution chemistry (Chang and Matzner, 2000). Stemflow has been considered as a spatially localized input of water into the soil causing preferential flow, which allowed rapid transport of contaminants to greater depths and then into the groundwater (Taniguchi et al, 1996).…”
Section: Introductionmentioning
confidence: 99%